Intracellular cytokine expression in invasive fungal sinusitis and its impact on patient outcome. Issue 9 (2nd September 2022) - Verma, P; Sikka, K; Verma, H; Thakar, A; Mitra, D K; Saurabh, A; Singh, G
Abstract: Background: Cell-mediated immunity plays an important role in host defence against fungal pathogens, regulated by differentiation of lymphocytes towards T-helper 1 or 2 cells. This study reports intracellular cytokine variation in terms of invasive fungal sinusitis type and outcome. Methods: The mononuclear leukocytes of 15 patients with invasive fungal sinusitis (mucormycosis in 8, aspergillus in 7) were stained with antibodies against intracellular cytokines, after fungal antigen stimulation and culture, and immunophenotyped. Patients were followed up for six months, with clinical course categorised as improvement, worsening or death. Results: The mean percentages of mononuclear cells producing interleukins 4, 5, 10 and 12, and interferon-γ, in the mucormycosis group were 0.575, 0.284, 8.661, 4.460 and 1.134, respectively, while percentages in the aspergillosis group were 0.233, 0.492, 4.196, 4.466 and 1.533. Cells producing interleukin 4 and 10 were higher in the mucormycosis group, while those producing interleukin-12 and interferon-γ were lower. Cells producing interleukins 4 and 12 were higher in patients with a poor outcome ( p -values of 0.0662 and 0.0373, respectively), while those producing interferon-γ were lower ( p = 0.0864). Conclusion: Adaptive cell-mediated immunity is expressed differently in two categories of invasive fungal sinusitis, and the cytokine expression pattern is related to prognosis.